Assessment of delivered dose in prostate cancer patients treated with ultra-hypofractionated radiotherapy on 1.5-Tesla MR-Linac - Gao, Lin-Rui; Tian, Yuan; Wang, Ming-Shuai; Xia, Wen-Long; Qin, Shi-Rui; Song, Yong-Wen; Wang, Shu-Lian; Tang, Yu; Fang, Hui; Tang, Yuan; Qi, Shu-Nan; Yan, Ling-Ling; et al. (Frontiers in Oncology, 2023)
Objective To quantitatively characterize the dosimetric effects of long on-couch time in prostate cancer patients treated with adaptive ultra-hypofractionated radiotherapy (UHF-RT) on 1.5-Tesla magnetic resonance (MR)-linac. Materials and methods Seventeen patients consecutively treated with UHF-RT on a 1.5-T MR-linac were recruited. A 36.25 Gy dose in five fractions was delivered every other day with a boost of 40 Gy to the whole prostate. We collected data for the following stages: pre-MR, position verification-MR (PV-MR) in the Adapt-To-Shape (ATS) workflow, and 3D-MR during the beam-on phase (Bn-MR) and at the end of RT (post-MR). The target and organ-at-risk contours in the PV-MR, Bn-MR, and post-MR stages were projected from the pre-MR data by deformable image registration and manually adapted by the physician, followed by dose recalculation for the ATS plan. Results Overall, 290 MR scans were collected (85 pre-MR, 85 PV-MR, 49 Bn-MR and 71 post-MR scans). With a median on-couch time of 49 minutes, the mean planning target volume (PTV)-V95% of all scans was 97.83 ± 0.13%. The corresponding mean clinical target volume (CTV)-V100% was 99.93 ± 0.30%, 99.32 ± 1.20%, 98.59 ± 1.84%, and 98.69 ± 1.85%. With excellent prostate-V100% dose coverage, the main reason for lower CTV-V100% was slight underdosing of seminal vesicles (SVs). The median V29 Gy change in the rectal wall was -1% (-20%–17%). The V29 Gy of the rectal wall increased by >15% was observed in one scan. A slight increase in the high dose of bladder wall was noted due to gradual bladder growth during the workflow. Conclusions This 3D-MR–based dosimetry analysis demonstrated clinically acceptable estimated dose coverage of target volumes during the beam-on period with adaptive ATS workflow on 1.5-T MR-linac, albeit with a relatively long on-couch time. The 3-mm CTV-PTV margin was adequate for prostate irradiation but occasionally insufficient for SVs. More attention should be paid to restricting high-dose RT to the rectal wall when optimizing the ATS plan.